Pengembangan Panduan Desain Ruang Kelas Berbasis Tematik di Sekolah Dasar - Ludfi Arya Wardana; Afib Rulyansah (Pascasarjana Universitas Negeri Malang, 2018)
Abstract: This research was aimed to produce design guidelines based on thematic classrooms conducted in class V schools of Tisnonegaran 1 Elementary School Probolinggo. This research and development method uses Borg & Gall which has been modified to be: (1) collection of information, (2) planning, (3) product development, (4) expert validation, (5) field trials, and (6) final products. The results of the development research showed that the results of the validation of learning technology experts were 97.2% and linguists were 90.6% and the readability test was 92.8%.The conclusion of thematic-based classroom design products in inclusive schools has expert validation levels and a high level of readability so that they can be used in improving the quality of learning. Suggestions for further development can use different classes and levels. Abstrak: Penelitian ini bertujuan untuk menghasilkan produk panduan desain ruang kelas berbasis tematik di sekolah dasar pada kelas V di SDN Tisnonegaran 1 Kota Probolinggo. Metode penelitian dan pengembangan ini menggunakan Borg & Gall yang telah dimodifikasi menjadi (1) pengumpulan informasi, (2) perencanaan, (3) pengembangan produk, (4) validasi ahli, (5) uji coba lapangan, dan (6) produk akhir. Hasil penelitian pengembangan menunjukkan hasil validasi ahli teknologi pembelajaran 97,2 % dan ahli bahasa 90,6 % dan uji keterbacaan 92,8%. Kesimpulan produk ruang kelas berbasis tematik di sekolah dasar mempunyai tingkat validasi ahli dan tingkat  keterbacaan yang tinggi sehingga dapat digunakan dalam peningkatan kualitas pembelajaran. Saran pengembangan lebih lanjut dapat menggunakan kelas dan jenjang yang berbeda.